1992
DOI: 10.1007/bf00027342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular details of tomato extensin and glycine-rich protein gene expression

Abstract: In a recent publication (Plant Molecular Biology 16: 547-565 (1991)), Showalter et al. described the isolation and initial characterization of fifteen extensin and extensin-like tomato cDNAs. These cDNAs were determined to fall into five distinct classes; class I and II clones encoded extensins, class III and V clones encoded glycine-rich proteins (GRPs), and class IV clones encoded a portion of a GRP sequence on one DNA strand and a portion of an extensin sequence on the other DNA strand. In this publication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 29 publications
(50 reference statements)
3
21
0
Order By: Relevance
“…These results confirm that ethylene is involved in the wound-regulated expression of the extA gene. The involvement of ethylene in extensin gene expression has been observed before; Showalter et al [19] showed that exposure of tomato plants to ethylene for 24 h in enclosed containers resulted in the accumulation of class 1 and class 2 extensin transcripts. As ethylene is involved in plant senescence, we suppose that the old senescent leaves (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These results confirm that ethylene is involved in the wound-regulated expression of the extA gene. The involvement of ethylene in extensin gene expression has been observed before; Showalter et al [19] showed that exposure of tomato plants to ethylene for 24 h in enclosed containers resulted in the accumulation of class 1 and class 2 extensin transcripts. As ethylene is involved in plant senescence, we suppose that the old senescent leaves (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…This contrasts with the results obtained by Showalter etal. [19] on the pattern of tomato extensin m R N A accumulation at and adjacent to the wound site, where expression of the Class 1 and Class 11 tomato extensins was primarily restricted to the wounded, cut ends. However, in the same study, the Class 111 tomato G R P transcripts accumulated at the cut ends and in the middle sections, showing a localised as well as a systemic response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 3, dicot GRPs, like extensin, are expressed in response to a variety of developmental and stress conditions (Condit and Meagher, 1987;Keller et al, 1988;van Kan et al, 1988;de Oliveira et al, 1990;Linthorst et al, 1990;Showalter et al, 1991Showalter et al, , 1992. Monocot GRPs are likewise expressed in response to a similar set of conditions (Gómez et al, 1988;Mundy and Chua, 1988;Lei and Wu, 1991;Didierjean et al, 1992).…”
Section: Regulated Expressionmentioning
confidence: 99%
“…The 0-75 kb band was almost indetectable 8 h after fumigation was ended (Eig, 1). A rapid increase in extensin transcript accumulation also has been shown in tomato stems and bean hypocotyl tissue upon wounding (Corbin et al, 1987;Showalter e« a/., 1992;Sauer et al, 1990), The rapid accumulation of extensin niRNAs is similar to the ozone induction of ^-1,3-glucanase mRNA in tobacco , as v^'ell as to the crossinduction of defensive genes in parsley (EckeyKaltenbach et al, 1994), The strong increase in extensin mRNA in ozone-treated pine needles contrasted with the response of wounded tomato leaves, for which no extensin mRNA accumulation is found (Showalter & Varner, 1987;Showalter et al, 1992), However, in tobacco leaves strong accumulation of wound-induced extensin mRNA is found, which is probably mediated by woundinduced ethylene formation (Memelink et al, 1993), Since exposure to ozone results in a rapid ethylene formation in other plant species (Tingey, Standley & Eield, 1976;Langebartels et al, 1991), it is possible that this also occurred in needles of Scots pine seedlings, so that a rapid and strong increase in extensin mRNA was mediated via this hormone.…”
Section: Resultsmentioning
confidence: 99%